Morphing concept based on thermoplastic fiber reinforced plastics - Goozen, H. van; Eijk, W. van der; Pijlman, H.H.; Docter, J.R. (Eccomas Proceedia, 2023)
Over the last few decades, much effort has gone into developing compliance-based morphing solutions for reducing drag generated by slots in the wing surfaces required for movables to operate. The main components of these morphing solutions are generally a continuous skin supported by a compliant internal structure. These components should provide sufficient stiffness to resist the aerodynamic loads and, as a contradiction, sufficient flexibility to allow deformation. Against this background, it is investigated whether a novel morphing concept is suitable for a winglet application with a tabto be used for large passenger aircraft wing load alleviation. This concept achieves flexibility and stiffness by combining a carbon fiber-reinforced thermoplastic skin lay-up with glass fiber reinforced thermoplastic so-called shear resistant flexures.
Peer-review under responsibility of the organizing committee of SMART 2023.